Theoretical Principles of the Russian Vocal School in the 19th Century - Martynova, Yulia A.; Martynov, Dmitry; Sukhova, Alina (Journal of History Culture and Art Research, 2018)
This article is devoted to formation of the Russian vocal school by examining the examples of M. Glinka, A. Varlamov, and H. Nissen-Saloman’s pedagogical techniques. Mikhail Ivanovich Glinka by right is considered the founder of the Russian school of singing. Alexander Varlamov for the first time tried to generalize theoretically practical experience of training in singing art. Henriette Nissen-Saloman, one more prominent representative of vocal pedagogics in Russia, made a lot of things for realization of experience of the European schools, first of all, French and Italian. Article leans on a complex of methods of the humanities, first of all historical and genetic and biographic. Its materials are of interest to historians of culture, researchers of the Russian music of the 19th century and experts in vocal pedagogics.